Adults with eosinophilic oesophagitis identify symptoms and quality of life as the most important outcomes. Issue 10 (30th October 2018) - Safroneeva, Ekaterina; Balsiger, Lukas; Hafner, David; Kuehni, Claudia E.; Zwahlen, Marcel; Trelle, Sven; Godat, Sébastien; Biedermann, Luc; Greuter, Thomas; Vavricka, Stephan; Straumann, Alex; Schoepfer, Alain M.
Summary: Background: Well informed patients who are in cohesive partnership with physicians and who have realistic expectations towards therapy are more likely to be adherent, which results in better disease control. Aim: To assess which therapy goals adults with eosinophilic oesophagitis consider relevant. Methods: Following refinement during three focus groups, a study brochure and questionnaire were sent to 148 patients. Patients ranked the importance (five levels) of short‐term (in the next 3 months) and long‐term (≥1 year) treatment effect on symptoms, quality of life (QoL), histologically‐detected inflammation and fibrosis, endoscopically‐detected inflammation, and stricture formation as well as achieving histological remission while asymptomatic. Patients' characteristics associated with treatment goals were identified using logistic regression. Results: Of 109 respondents (mean age 43 years), 85 were men. Over 90% chose symptoms and QoL improvement as important short‐ and long‐term therapy goals. A greater proportion attributed more importance to long‐term reduction in endoscopic (90% vs 73%, P < 0.001) and histological (81% vs 62%, P = 0.002) inflammation, and histologically‐detected fibrosis (79% vs 64%, P = 0.018) when compared to short‐term reduction in these features. Patients (88%) ranked achieving histological remission while being asymptomatic as important. Gender, therapy use, education level, QoL, symptom severity, and history of dilation were associated with patients' choice of treatment goals. Conclusions: Patients attributed most importance to improvement in symptoms and QoL. Reduction in biological activity was judged less important, but more relevant in the long‐ compared to the short‐term.